MAKNA PERTUNJUKAN WAYANG KRUCIL DALAM BERSIH DESA MANGANAN JANJANG - Budi Utomo; S., Sarwanto (Institut Seni Indonesia Surakarta, 2016)
The meaning of krucil puppet show in the ceremony of puryfying village Manganan Janjang. Thepurpose of this study is to describe and to understand the meaning of krucil puppet show in aseries of Cleaning Village Manganan Janjang. The problems studied include: what the meaning ofa krucil puppet show in a series of purifying Village Manganan Janjang is? Research materials arecollected through library study, interview, and direct observation to the puppet show in a series ofpurifying Village Manganan Janjang with title Bedhah Medhayin at June 6, 2013, by Ki Lamto thepuppeteer. This study uses the analysis of the meaning by using descriptive interpretativemethod. The results showed that: The meaning of the show related to the meaning of title, andthe meaning of the symbol. The meaning is related to meaning symbol contextual of the show.Keywords: Krucil puppet, manganan Janjang, the meaning.